Anesthesia for Maternal–Fetal Interventions: A Consensus Statement From the American Society of Anesthesiologists Committees on Obstetric and Pediatric Anesthesiology and the North American Fetal Therapy Network. (12th October 2020) - Chatterjee, Debnath; Arendt, Katherine W.; Moldenhauer, Julie S.; Olutoye, Olutoyin A.; Parikh, Jagroop Mavi; Tran, Kha M.; Zaretsky, Michael V.; Zhou, Jie; Rollins, Mark D.
Abstract : Maternal–fetal surgery is a rapidly evolving specialty, and significant progress has been made over the last 3 decades. A wide range of maternal–fetal interventions are being performed at different stages of pregnancy across multiple fetal therapy centers worldwide, and the anesthetic technique has evolved over the years. The American Society of Anesthesiologists (ASA) recognizes the important role of the anesthesiologist in the multidisciplinary approach to these maternal–fetal interventions and convened a collaborative workgroup with representatives from the ASA Committees of Obstetric and Pediatric Anesthesia and the Board of Directors of the North American Fetal Therapy Network. This consensus statement describes the comprehensive preoperative evaluation, intraoperative anesthetic management, and postoperative care for the different types of maternal–fetal interventions.